Resenha: ORO, Ivo Pedro. O fenômeno religioso: como entender. São Paulo: Paulinas, 2013. 189 p. - Leal, Jair Souza (Numen, 2018)
Resenha do livro O Fenômeno religioso: como entender, de Ivo Pedro Oro.